Association between Smoking Habits and Outcomes of COVID-19 Patients in Persahabatan Hospital, Jakarta - Ayesya Nasta Lestari; Feni Fitriani Taufik; Agus Dwi Susanto (Jurnal Respirologi Indonesia, 2024)
Background: : Factors related to the severity and the outcome of coronavirus disease 2019 (COVID19) are emerging subjects of interest to be studied. Smoking has long been known to have a negative impact on the response to infection. The purpose of this study was to determine the association between smoking habits with the severity, the length of hospitalization and the outcome of COVID19 patients.Methods: This study was a prospective cohort study of COVID-19 patients admitted at Persahabatan Hospital, Jakarta, Indonesia. Subjects were included by consecutive sampling from August to October 2021. Subjects were assigned into smokers and non-smokers group. All subjects were assessed for their severity, length of hospitalization and outcome; in smoking patients, the Brinkman Index (IB) and the Fagerström Test for Nicotine Dependent (FTND) score were also recorded. Statistical tests were then carried out to assess the significant association between smoking history and the degree of severity, length of hospitalization and outcome of COVID-19 in all patients and the FTND and IB scores with the degree of severity, length of hospitalization and outcome of COVID-19 in smokers.Results: Authors found that 39/100 (39%) of participants were smokers. Smoking history had a correlation with the outcome (p=0.001) but not with the degree of severity (p=0.410) and length of hospitalization (p=0.780). Among subjects with smoking history, there were correlations found between FTND and the degree of severity and the outcome (p=0.022 and p=0.012), but not with the length of hospitalization (p=0.716). The Brinkman Index was correlated with only the degree of severity (p=0.020).Conclusion: Our study found that smoking habits were correlated with the degree of severity and outcomes in COVID-19 patients.